Rasionalitas Di Balik Perlakuan Masyarakat Terhadap Hewan Kerbau Di Desa Tenganan Pegringsingan, Kecamatan Manggis, Kabupaten Karangasem, Bali. - Widana, Made; Arsana, I Gst. Ketut Gde; ., Aliffiati (Humanis, 2016)
Bufallo has such an important role in life of Indonesian society. Generally, bufallo is used to be a plougher as ploughing the rice field, while the flesh and milk could be utilized as the nutrient needs, as well as the horns and bones, could be used as the materials of handicraft. Buffalo’s safeguarding, generally is being stabled and its nose is pinned as a sign of livestock. In Tenganan Pegringsingan village, buffalo is not used as a livestock and the local people do not consume its flesh and milk. The buffalos are freely live around the village without being stabled or pinned. The way of local people treating the buffalo is special. The physical treatment of local people could be seen from the way they called the buffalo as Jero Gede, they do not use it as a plougher, so do its flesh and milk, are not consumed by them. The symbolic treatment of buffalo could be seen from the special ceremony for the buffalo, and two holy temples as the places of sacrifice and respect towards buffalo as well as The God who trusted as the owner of buffalo, Kandang Temple and Raja Purana Temple. The special rationality of local people to the buffalo is a type of local society wisdom. The rationalities such as; maintained the social relationship continuously, maintained the buffalo race, ecology, cultural conservation, and protection of magic threat and diseas.